Família e TV: mais que dominação e subordinação. - Zacarias, Mônica Costa de Oliveira (2005)
This work analises the social relationship between Television and the Family though the resignification of individuals about Television messages and the speeches that they make about Family. Firstly, the objective is to understand if the principles, values and beliefs constructed and communicated (repassed) inside the Family filter the messages from the Mass Media. Secondly, if there still exists a family culture able to forge identity against so many cultural exchanges. Thirdly, what the function of this identity in the production of senses is. In session 1 and 2, a general approach about the dissemination of Mass Media in Society and the pertinence of the work is presented. Session 3 is about the method used: a qualitative research, with thirteen families from Natal-RN, situated in the Middle Class. The theorical base is considered in the fourth session where the reference to the evolution of the Family is made, with enphasis on the Middle Class and some theories that analyze the pheomenom of the Mass Media , specially in the second half of twentieth century. In session 5 and 6, the research data is presented and analyzed. Finally, in the last session, as a conclusion it can be said that the value of the Family as emotional support is reforced by the speeches and practices that interfere in the signification procces, singular aspects, as well as the social repertoire constructed per si and by institutions (including the family) moreover, mediative message is assimilated by the receiver and becomes understood inside the learned speeches during the receiver‟s history of life, although these messsages are also components in the construction of these repertoire.